Gender determination by radiomorphometric analysis of permanent mandibular canines using orthopantomograms: an observational study: An observational study (Bulletin of the International Association for Paleodontology, 2024)
Introduction:Identification of unknown human remains is mainly done by establishing a biological profile in which sex determination is one of the key identifiers. The present study aims to analyze the sexual dimorphism exhibited by mandibular canines in the South Indian population.Materials and Method:A total of 250 orthopantomograms of adults aged 20 to 59 years were selected for the present observational study. The maximum mesiodistal diameter of the permanent mandibular canines was measured using Image J software. The maximum mesiodistal crown diameter at the height of the contour and the cervical line was considered.Results :An accuracy of 66.8% was obtained by the derived logistic regression formular. The maximum mesiodistal diameter at the HOC and cervix is higher in males compared to females. The index of Sexual Dimorphism calculations showed a higher value at the cervix than at the height of contour.Conclusion:Mesiodistal radiomorphometric measurements of mandibular canine can aid in gender determination in forensic odontology and paleodontology. The radiomorphometric measurements at the cervix show a better sexual dimorphism than the maximum crown diameter. Radiomorphometric measurements can be used as an aid in establishing the biological profile of unknown human remains.